Morphometric variation and ecological niche differentiation in Hyophila apiculata and H. involuta from karst microhabitats in Kanchanaburi, Thailand - WEERACHON SAWANGPROH (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Sawangproh W. 2024. Morphometric variation and ecological niche differentiation in Hyophila apiculata and H. involuta from karst microhabitats in Kanchanaburi, Thailand. Biodiversitas 25: 4551-4560. Karst environments, characterized by limestone and dolomite formations, host diverse ecosystems shaped by unique geological features such as sinkholes, caves, and underground rivers. These landscapes foster adaptations among flora and fauna, showcasing phenotypic plasticity that enables species to thrive in challenging conditions. This study examines the morphometric variation between Hyophila apiculata M.Fleisch. and H. involuta (Hook.) A.Jaeger in arid karst microhabitats of Kanchanaburi Province, Thailand. Surveys conducted across 86 sampling points revealed predominantly allopatric populations, with H. apiculata present in 26 sites (30%) and H. involuta in 58 sites (68%). Sympatric occurrences were rare, found at only two points (2%). Leaf morphometric analyses demonstrated that H. involuta exhibits wider leaves and larger leaf areas compared to H. apiculata, which features longer and wider median and apical leaf cells with thicker cell walls. Principal Component Analysis (PCA) indicated distinct morphological clusters for the two species, though some overlap was observed, suggesting the possibility of hybridization or transitional forms. These findings underscore the ecological niche differentiation and adaptive strategies of these moss species, enhancing our understanding of plant diversity and resilience in calcareous environments. This research contributes to the broader conservation efforts in these sensitive areas, emphasizing the need for preserving karst ecosystems that harbor unique biological communities and serve as indicators of environmental health. Such insights are critical for developing effective conservation strategies aimed at safeguarding the rich biodiversity found in karst landscapes.